Relationship Between Sedentary Lifestyle and Fiber Intake Primary Dysmenorrhoea in Overweight Adolescent Girls - Hidayatusy Syukrina Puteri; Yulia Lanti Retno Dewi; Sri Mulyani (Jurnal Penelitian Pendidikan IPA, 2023)
Overweight female adolescents (FA) have a 36.8% risk of primary dysmenorrhea (PD) compared to FA with normal nutritional status. PD can be minimized by increasing daily physical activity and consumption of fiber found in vegetables and fruit by nutritional adequacy rates. This study aimed to analyze the relationship between a sedentary lifestyle and daily fiber intake on PD in overweight FA in Padang. This research method is cross-sectional and conducted at MAN 1 and SMA 1 Muhammadiyah Padang. The research subjects were all female students who met the restriction criteria with a total of 38 people. Data collection was carried out by anthropometric measurements and interviews using the NRS, ASAQ, and SQ-FFQ questionnaires. The results of data analysis using the Spearman rank correlation test showed that there was a relationship between fiber intake and the pain scale in primary dysmenorrhea (p=0.007), and a sedentary lifestyle was not related to primary dysmenorrhea (p=0.73). The conclusion is that the primary dysmenorrhea pain scale is associated with daily fiber intake consumed according to the nutritional adequacy rates of overweight female adolescents in Padang.